Organizational Culture and Child-Friendly Schools: Insights for Early Childhood Education - Supriyono, Eko; Nurhajah, Siti; Ratnawati, Eka; Munfa'atin, Djohar; Herman, Maman (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study explores how a conducive learning environment in P.A.U.D. affects early childhood development and public trust in schools. This study aims to identify critical factors that create a positive learning environment and provide practical recommendations for educators and policymakers. This study uses a qualitative approach with a case study method, where data are collected through in-depth interviews, observations, and documentation. The data obtained are analyzed using Milles and Huberman’s interactive analysis technique, which involves the process of data reduction, data presentation, and conclusion. The analysis results show that collaboration between teachers, staff, parents, and children is essential in building a supportive learning atmosphere and increasing parental trust in the quality of education. Emotional support from teachers and the active participation of parents in school activities have proven crucial in creating a conducive environment. The conclusion of this study confirms that a conducive learning environment not only increases children’s motivation and achievement but also strengthens the relationship between schools and the community. The main contribution of this study is to provide an effective strategy for developing collaboration between schools, parents, and the community to create an optimal learning environment.